Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Evaluation of ballistics euthanasia applied to stranded cetaceans using ethological and post-mortem computed tomography assessment - Rebecca M. Boys; Brian C. W. Kot; Gordon Lye; Ngaio J. Beausoleil; Stuart Hunter; Karen A. Stockin (Veterinary Research Communications, 2024)
Debilitated stranded cetaceans with low survival likelihood, may require euthanasia to avoid further suffering. Euthanasia can involve chemical or physical methods, including ballistics. Ballistics should cause instantaneous, permanent insensibility through brainstem disruption. Despite wide application, there is limited understanding of ballistics-related welfare outcomes. We opportunistically examined behaviour of three maternally-dependent cetaceans following shooting and the related cranial disruption post-mortem using computed tomography (PMCT). Our aim was to understand whether a ‘humane death’, i.e., euthanasia, was achieved. Each animal was shot using different projectile types: soft non-bonded, solid, and soft bonded. In two animals, insensibility was not immediately assessed following shooting, although both were reported as ‘instantaneously insensible’. From our analysis, all animals displayed musculoskeletal responses to shooting, including peduncle stiffening and slack lower jaw, followed by musculature relaxation 24-, 10.3- and 20.8-seconds post-ballistics, respectively. The animal shot with a soft non-bonded projectile also displayed agonal convulsions and tail-lifting for 16-seconds post-shot; these were not observed for solid or soft bonded projectiles. PMCT findings indicated projectile disruption to the brainstem and/or spinal cord likely to cause near-instantaneous insensibility. However, extra-cranial wounding was also evident for the soft non-bonded projectile, highlighting potential for additional welfare compromise. Our results demonstrate that ballistics can achieve a relatively rapid death in young, stranded cetaceans, but careful equipment selection is required. To ensure a humane death, verification of insensibility must be undertaken immediately following shooting. Further studies should be undertaken to improve knowledge of appropriate procedures and equipment for euthanasia, ensuring humane deaths for compromised cetaceans.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Our future in the Anthropocene biosphere - Carl Folke; Stephen Polasky; Johan Rockström; Victor Galaz; Frances Westley; Michèle Lamont; Marten Scheffer; Henrik Österblom; Stephen R. Carpenter; F. Stuart Chapin; Karen C. Seto; Elke U. Weber; et al. (Ambio, 2021)
The COVID-19 pandemic has exposed an interconnected and tightly coupled globalized world in rapid change. This article sets the scientific stage for understanding and responding to such change for global sustainability and resilient societies. We provide a systemic overview of the current situation where people and nature are dynamically intertwined and embedded in the biosphere, placing shocks and extreme events as part of this dynamic; humanity has become the major force in shaping the future of the Earth system as a whole; and the scale and pace of the human dimension have caused climate change, rapid loss of biodiversity, growing inequalities, and loss of resilience to deal with uncertainty and surprise. Taken together, human actions are challenging the biosphere foundation for a prosperous development of civilizations. The Anthropocene reality—of rising system-wide turbulence—calls for transformative change towards sustainable futures. Emerging technologies, social innovations, broader shifts in cultural repertoires, as well as a diverse portfolio of active stewardship of human actions in support of a resilient biosphere are highlighted as essential parts of such transformations.

Population density–range size relationship revisited - Maria Novosolov; Gordon H. Rodda; Alexandra C. North; Stuart H. M. Butchart; Oliver J. S. Tallowin; Alison M. Gainsbury; Shai Meiri (Global Ecology and Biogeography, 2017)
Aim The species population density–range size relationship posits that locally abundant species are widely distributed. However, this proposed pattern has been insufficiently tested. The few tests conducted were usually limited in scale and gave conflicting results. We tested the generality of the positive population density–range size relationship. We then studied whether similar environmental niche requirements are correlated with range size and with population density to search for mechanisms driving the hypothesized link between population density and range size. Location Worldwide. Methods We collected data on population density, range size and environmental niche for a global dataset of 192 lizard, 893 bird and 350 mammal species. Assessing the relationship between population density and range size and environmental niche parameters, we corrected for phylogenetic relationships, body mass, diet and study area. Results Our findings reveal that density had a weak negative correlation with bird range size and was unrelated to lizard and mammal range size. These trends were consistent at the global scale and across the biogeographical realms. Range size was related to relatively similar environmental niche parameters in all groups. Population density, however, was explained by taxon‐specific factors and was therefore unrelated to range size by common causation. Main conclusions We suggest that the positive relationship between population density and range size identified in previous studies might be an artefact arising through incomplete sampling of range sizes. Our results indicate that the mechanisms shaping population density and range size may be independent.

Combining plant resistance and a natural enemy to control Amphorophora idaei - Carolyn Mitchell; Scott N. Johnson; Stuart C. Gordon; A. Nicholas E. Birch; Stephen F. Hubbard (BioControl, 2010)

Early Life Stress on Brain Structure and Function Across the Lifespan: A Preliminary Study - Donna L. Seckfort; Robert Paul; Stuart M. Grieve; Brian Vandenberg; Richard A. Bryant; Leanne M. Williams; C. Richard Clark; Ronald A. Cohen; Steven Bruce; Evian Gordon (Brain Imaging and Behavior, 2008)

Twenty-Five Years of the Clean Water Act: How Clean Are Forest Practices? - George G. Ice; Gordon W. Stuart; Jack B. Waide; Lloyd C. Irland; Paul V. Ellefson (Journal of Forestry, 1997)